Modal-based synthesis of passive electrical networks for multimodal piezoelectric damping. (15th August 2022) - Raze, Ghislain; Dietrich, Jennifer; Lossouarn, Boris; Kerschen, Gaëtan
Abstract: This work presents a new approach to design an electrical network which, when coupled to a structure through an array of piezoelectric transducers, provides multimodal vibration mitigation. The characteristics of the network are specified in terms of modal properties. On the one hand, the electrical resonance frequencies are chosen to be close to those of the targeted set of structural modes. On the other hand, the electrical mode shapes are selected to maximize the electromechanical coupling between the mechanical and electrical modes while guaranteeing the passivity of the network. The effectiveness of this modal-based synthesis is demonstrated using a free–free beam and a fully clamped plate. Highlights: Passive electrical networks are synthesized based on their modal properties. The electrical resonance frequencies are close to the mechanical ones. The electrical mode shapes are optimized for maximum coupling. Passivity constrains the maximum electrical mode shape amplitudes. The approach is illustrated on a free–free beam and a fully clamped plate.